Affecting Factors Fear of Childbirth Based on the Theory of Planned Behavior in Pregnant Women in Aleshstar in 2015 - Monir Yosefvand; Mahboobeh Khorsandi; Nasrin Roozbahani; Mehdi Ranjbaran (Hamadan University of Medical Sciences, 2017)
Background: Fear of childbirth in pregnant women is a common problem that often leads to the demand for cesarean section. Due to the complications of cesarean delivery for mother and baby, doing researches on factors predicting fear of childbirth is essential. Method: This is a cross-sectional analytical study. 200 pregnant women were selected in Aleshtar city by simple random sampling in 2015. Data collection tools included two questionnaires. One researcher-made questionnaire, including structures of planned behavior theory including attitudes, subjective norms, perceived behavioral control and behavioral intention; this was a standardized questionnaire for fear of childbirth. To analyze the data, software Spss20, one-way ANOVA and Pearson correlation and regression were performed. Results: 71 of the 200 women (35.5 percent) were going to do a cesarean section. As a result, an inverse correlation was observed between attitude structures and perceived behavioral control with fear of childbirth.  Attitude was the most important predictor of pregnant women's fear (Beta=-0.29). In terms of fear, attitude, subjective norm and perceived behavioral control between the women who wanted natural childbirth, and women who wanted a cesarean section, there were statistically significant differences. Conclusion: It is suggested to emphasize on factors such as positive attitude and perceived behavioral control, at the time of designing educational interventions for reducing the childbirth fear and unnecessary caesarean.